Facial Aesthetic Priorities and Concerns: A Physician and Patient Perception Global Survey. (9th October 2021) - Fabi, Sabrina; Alexiades, Macrene; Chatrath, Vandana; Colucci, Ligia; Sherber, Noëlle; Heydenrych, Izolda; Jagdeo, Jared; Dayan, Steven; Swift, Arthur; Chantrey, Jonquille; Stevens, W Grant; Sangha, Sara
Abstract: Background: Minimally invasive and noninvasive facial aesthetic treatments are increasingly popular, and a greater understanding of patient perspectives on facial aesthetic priorities is needed. Objectives: The authors surveyed facial aesthetic concerns, desires, and treatment goals of aesthetically conscious men and women, and physicians, in 18 countries. Methods: This was a global, internet-based survey on desired appearance and experiences with, or interest in, facial aesthetic treatments. Eligible respondents were aesthetically conscious adults (21-75 years). Eligible aesthetic physicians were required to see ≥30 patients per month for aesthetic reasons, have 2 to 30 years of experience in clinical practice, and spend ≥70% of their time in direct patient care. Results: A total of 14, 584 aesthetically conscious adults (mean age, 41 years; 70% women) and 1315 aesthetic physicians (mean age, 45 years; 68% men) completed the survey. Most respondents (68%) reported that aesthetic procedures should be sought in their 30s to 40s; physicians recommended patients seek treatment earlier. Respondents expressed greatest concern over crow's feet lines, forehead lines, facial skin issues, hair-related concerns, and under-eye bags or dark circles; in contrast, physicians tended to underestimate concerns about under-eye bags or dark circles, mid-face volume deficits, and skin quality. Although both physicians and respondents cited cost as a major barrier to seeking aesthetic treatments, respondents also emphasized safety, fear of injections or procedure-related pain, and concern about unnatural-looking outcomes. Conclusions: This global survey provides valuable insight into facial aesthetic concerns and perspectives that may be implemented in patient education and consultations to improve patient satisfaction following aesthetic treatments.